Numerical simulation of blood flow in a stenotic artery - Luísa C. Sousa (2009)
The purpose of this paper is to develop a numerical computational methodology for the simulation of blood flow in a stenotic artery. As a first approach biochemical and mechanical interactions between blood and vascular tissue are neglected and the flow is considered through a rigid tube. Considering a non-Newtonian model numerical results are obtained for velocity and shear stresses distributions.